Aktivasi Zeolit Alam Lampung sebagai Adsorben Karbon Monoksida Asap Kebakaran - Yuliusman Yuliusman (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
This study aims to absorb the carbon monoxide (CO) gas using Lampung natural zeolite as an adsorbent. Natural Zeolite has porous crystal structure, large surface area, high thermal stability, non-toxic, and effective. Natural zeolites contain many impurities, then it must be activated. Activation of natural zeolite was done by soaking in a solution of 2% HF for 10 minutes with stirring. Furthermore, dealumination natural zeolite carried out  by soaking in a solution of 6 M HCl for 30 minutes. Zeolite was soaked with a solution of 0.1 M NH4Cl and then was calcined.  Then Activated Natural zeolite was tested the adsorption of cabon monoxide gas from burning tissue paper. Variations in particle size of the zeolite is 53-106 μm, 106-150 μm and 150-212 μm. The results showed that activated natural zeolite with a particle size of 53-106 microns can adsorb CO gas at 379 ppm (12.2%) of the initial concentration for 20 minutes.